Ethnomathematics: Mathematical Exploration on Batik Gedog Tuban - Ervinawati, Yulia (Universitas Negeri Surabaya, 2019)
Batik Gedog Tuban is a famous Batik in Tuban. This batik has a variety of motifs/patterns with a variety of colors. This research is a qualitative descriptive with an ethnographic approach, and this research aims to analyze the mathematical value within Batik Gedog Tuban. Data collections were conducted by the study of literature, observation, interview, note, and documentation. The results show that there are several mathematical concepts contained in Batik Gedog Tuban, such as geometry concepts, geometry transformation, and congruence.